KEEFEKTIFAN PENDEKATAN SAINTIFIK DENGAN MENGGUNAKAN PBP DALAM MENINGKATKAN MOTIVASI BERPRESTASI DAN JIWA KEWIRAUSAHAAN SISWA - Andika Apriawan; Sugiharsono Sugiharsono (Yayasan Pendidikan Intan Cendekia, 2018)
This study was a quasi-experimental research using one experimental group and two control groups. The population of this study were all students of class X MAN 2 Mataram. The technique of taking samples used random (random sampling). The results of this research show that: 1) the scientific approach using project-based learning (PJBL) method is effective in improving students’ achievement motivation and entrepreneurial spirit in economic subjects with 0.04 of significance level, and 2) the scientific approach project-based learning method is more effective than conventional teaching methods in improving students’ achievement motivation and entrepreneurial spirit in economic subjects with 0.04 of significance level in each variable for the experimental class, whereas first control class in each variable is 0.056 and 0.090, and then the second control class in each variable was 0.483 and 0.555.